Design of experiments for chemical, pharmaceutical, food, and industrial applications - Carrillo-Cedillo, Eugenia Gabriela, 1966- (Advances in chemical and materials engineering (ACME) book series., 2020)
"This book seeks to increase the use of design of experiments to optimize and improve analytical methods and productive processes in order to use less resources and time"--